Clusters in automotive and information & communication technology : innovation, multinationalization and networking dynamics - Welfens, Paul J.J (Springer Berlin Heidelberg, 2012)
Information & communication technology (ICT) and the automotive sector are two of the most important industries in the EU and the US. The EU's eastern expansion and economic globalization have reinforced competition on the one hand; on the other hand the importance of outsourcing and off-shoring has increased. Against this background the intensification of innovation dynamics becomes crucial - and with them the role of regional innovation clusters. The analysis examines seven regions and six EU countries. The focus is on cluster and network dynamics in both industries, as regional ICT clusters are playing an increasingly central role in many European regions. Specialization and structural change in the automotive sector are highlighted, and new strategic approaches for multinational companies and changes in policy options are identified.